MICROBIAL PATTERNS AND DRUG SENSITIVITY TEST OF BACTERIAL AND FUNGAL INFECTION IN COVID-19 PATIENTS AT ADAM MALIK HOSPITAL, MEDAN, INDONESIA - SIBARANI, Ursula Regina Florense; SINAGA, Bintang Yinke Magdalena; MUNTASIR, Muntasir; MUTIARA, Erna (African Journal of Infectious Diseases (AJID), 2024)
Background: Bacteria or fungi in COVID-19 involves several mechanisms that can affect immune system and also can increase severity of symptoms. The incidence of bacterial or fungal infections is common in patients with viral respiratory tract infections but the prevalence of bacterial or fungal infections and drug sensitivity test pattern in COVID-19 patients is still not well understood. The aim of this study was to determine the bacterial or fungal infections and drug sensitivity test pattern in COVID-19 patients. Methods: This is retrospective observational descriptive research with a cross-sectional design. The data was obtained from the COVID-19 patients medical records at Adam Malik Hospital, Medan, Indonesia Result: A total population of 100 COVID-19 patients were included, with bacterial infections in 26 patients (26%), fungi in 5 patients (5%), bacteria and fungi in 5 patients (5%). The most common bacterial pathogen was Acinetobacter baumannii in 14 patients (45.1%), followed with Klebsiella pneumonia in 5 patients (16.1%), Pseudomonas aeruginosa in 5 patients (16.1%) and Escherichia coli in 3 patients (9.6%). The most sensitive antibiotic in Acinetobacter baumannii was Amikacin (57.14%), Trimethoprim/sulfamethoxazole (40.0%), Ampicillin sulbactam (28.6%), and Meropenem (21.4%). The most common fungal infection was Candida albicans in 5 patients (50.0%) and mostly sensitive to Fluconazole, Voriconazole, Caspofungin, Amphotericin B, Micafungin and Flucytosine (60.0%). Conclusion: Bacterial and fungal infections can occur in COVID-19 patients. The data on pathogen patterns and sensitivity tests in this study can be the basis for administering antibiotics empiric in hospital for COVID-19 patients.